Posted by **Sue** on Thursday, November 1, 2012 at 10:07am.

(x+1)/3 + (3x - 2)/4 = (x + 5)/8 - (7x - 1)/6 - 37/12

I need the steps please...I know the answer

- Math -
**Steve**, Thursday, November 1, 2012 at 10:21am
first, look for a common denominator. LCM(3,4,8,6,12) = 24

So, multiply it all by 24:

8(x+1) + 6(3x-2) = 3(x+5) - 4(7x-1) - 74

expand the terms:

8x+8+18x-12 = 3x+15-28x+4-74

8x+18x-3x+28x = 15+4-74-8+12

51x = -51

x = -1

- Math -
**Sue**, Thursday, November 1, 2012 at 11:20am
Steve, I see it clearly now....thank you

- Math -
**Steve**, Thursday, November 1, 2012 at 12:01pm
After a few dozen more, these will be no problem.

## Answer this Question

## Related Questions

- Algebra - Find the product of (x^2 - 3x + 5) with the quotient of (10x^6 - 15x^5...
- Algebra - Simplify the complex rational expression 3/(x+5)+ 6/(x+3) ÷ (3x+13)/(x...
- math - how do u divide fractions? i really need help with this. i need to know ...
- Calculus Help Please!!! - show all of the algebraic steps in finding lim x->0...
- Math - 3x-4 to y+15 is constant and y=3 when x=2 then when y=12, x equals? My ...
- math help - Thank you for helping me with the last problem Reiny and Bosnian. ...
- Math - I need help with this math question: What percent of 400 is 12? Can you ...
- math - Consider the following students method of solving the proportion 8/5 = 20...
- math ergent please please... - 10.a)Solve the inequality x^3-5x^2+2x+8<0 by i...
- Math - OK, I have had trouble with math, 'C' average, and we are learning ...